The Effects of Applied Short-Term Psychodynamic Therapy on The Depressive Symptoms of Patients with Major Depressive Disorder - Phonchan, Santhat; Soonthonchaiya, Rangsiman; Jirarode, Angkana (Journal of The Royal Thai Army Nurses, 2023)
The purpose of this Quasi-experimental research aimed to examine an applied short-term psychodynamic therapy program on the depressive symptoms of patients with major depressive disorder. The subjects of this study were 54 patients. The subjects were randomly assigned to the experimental and control groups with 27 patients in each group. The experimental group participated in the applied short-term psychodynamic therapy program, The duration of the individual intervention was eight sessions, each session lasting 45 to 60 minutes. The control group received routine care. The research instruments consisted of 1) the applied short-term psychodynamic therapy program, which was validated by three experts, and 2) the Hamilton rating scale for depression (Thai version), whose reliability was determined with a Cronbach’s alpha coefficient of .78. The data were analyzed using descriptive statistics and t-test. The results of the study were as follows.1) The mean score for the depressive symptoms of the experimental group after participating in the applied short-term psychodynamic therapy program (M = 11.15, SD = 1.70) was significantly lower than the mean score for the depressive symptoms (M = 21.96, SD = 1.76) before participating in the program (t = 21.97, p < .05). 2) The mean difference in the depressive symptoms between the pretest and posttest depressive mean score for the experimental group that participated in the applied short-term psychodynamic therapy program (1 = 10.81, SD = 1.70) was significantly greater than that of the control group that received routine care (2 = 6.63, SD = 1.87) (t = 7.09, p <.05). In summary, the applied short-term psychodynamic therapy program was able to effectively reduce the depressive symptoms of patients with major depressive disorder. Thus, the program can be used as an alternative activity or program to reduce the depressive symptoms of this group of individuals.